Implementasi Peraturan Daerah Kota Medan Nomor 10 Tahun 2012 Tentang Retribusi Pelayanan Kebersihan - Siregar, Irin Hanafiah; Kadir, Abdul; Muda, Indra (Universitas Medan Area, 2019)
This study aims to determine the application and process of implementing regional regulation number 10 of 2012 concerning levies on cleaning services in Medan Tembung Subdistrict, Medan City. This study used descriptive qualitative method. Data collection techniques carried out were interviews, observation and documentation. Implementation of Regional Regulation Number 10 of 2012 concerning cleaning service levies in Medan Tembung Subdistrict (Medan City) has been running quite well in terms of the application of performance in the field and the readiness of the workforce to implement the regulation has been quite good. The constraints faced are infrastructure resource factors that have not been sufficiently adequate in implementing the performance carried out such as typper cars and motorized becak (Betor), which are still lacking in the needs needed.